PENINGKATAN LITERASI GURU SMA NEGERI PLUS SUKOWONO DENGAN PELATIHAN PENULISAN BUKU BER-ISBN - Murtikusuma, Randi Pratama; Afifah, Ngizatul; Mutammam, Muhamad Badrul; Salim, Abdurrahman (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2025)
The book writing training with an International Standard Book Number (ISBN) for teachers at SMA Negeri Plus Sukowono was carried out as an effort to improve literacy and writing productivity among educators. Teachers’ enthusiasm for writing was quite high, but most still faced difficulties in preparing systematic manuscripts and understanding the procedures for publishing ISBN books. This community service activity was implemented using a participatory approach through three main stages, namely needs identification, material delivery, and writing assistance. The training materials covered finding book ideas, understanding structures and types of books, and avoiding plagiarism in writing. The activity was conducted in the form of interactive lectures, hands-on drafting practice, and question-and-answer sessions. The final results showed a significant increase in participants’ understanding of the training materials. Some participants successfully compiled outlines and began writing their own book manuscripts. This activity served as an initial step in establishing a school literacy culture centered on teachers’ work, while also opening up opportunities for higher-quality publications in the future. ABSTRAK Kegiatan pelatihan penulisan buku dengan International Standard Book Number (ISBN) bagi guru SMA Negeri Plus Sukowono dilaksanakan sebagai upaya untuk meningkatkan literasi dan produktivitas karya tulis di kalangan pendidik. Antusiasme guru dalam menulis cukup tinggi, tetapi sebagian besar masih menghadapi kendala dalam menyusun naskah yang sistematis dan memahami prosedur penerbitan buku ber-ISBN. Pengabdian ini dilaksanakan dengan pendekatan partisipatif melalui tiga tahapan utama, yaitu identifikasi kebutuhan, penyampaian materi, dan pendampingan penulisan. Materi pelatihan mencakup menemukan ide penulisan buku, sistematika dan jenis-jenis buku, serta menghindari plagiarisme dalam penulisan buku. Kegiatan ini berlangsung dalam bentuk ceramah interaktif, praktik langsung penyusunan draf buku, serta sesi tanya jawab. Hasil akhir menunjukkan peningkatan signifikan dalam pemahaman peserta terhadap materi pelatihan. Sebagian peserta berhasil menyusun kerangka dan mulai menulis naskah buku masing-masing. Kegiatan ini menjadi langkah awal dalam membangun budaya literasi sekolah berbasis karya guru, sekaligus membuka peluang bagi lahirnya publikasi yang lebih berkualitas di masa mendatang.